1990
DOI: 10.1016/0020-7292(90)90514-l
|View full text |Cite
|
Sign up to set email alerts
|

Fundal height in normal pregnant Nigerian women: Anthropometric gravidogram

Abstract: Fundal height measurements in centimeters (FH) have always been an objective method of evaluating fetal growth in pregnancy. The popular Mcdonald's rule refers mainly to caucasions unfortunately. Since FH may actually vary in an anthropological sense it was considered necessary to apply Mcdonald's rule to African subjects. Pregnant Nigerian women were studied to observe how their fundal height values compared with those obtained for caucasian women in western communities. A gravidogram was derived for the 10th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…We were concerned that an external reference may introduce error in the estimation of gestational age based on SFH. The need for internal SFH references has been assessed in rural areas of developing countries 23,24 with mixed conclusions. We found that SFH in this sample was very small compared with published references 13,23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were concerned that an external reference may introduce error in the estimation of gestational age based on SFH. The need for internal SFH references has been assessed in rural areas of developing countries 23,24 with mixed conclusions. We found that SFH in this sample was very small compared with published references 13,23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The need for internal SFH references has been assessed in rural areas of developing countries 23,24 with mixed conclusions. We found that SFH in this sample was very small compared with published references 13,23 , 24 . Whether this difference is due to technical error or a systematically smaller SFH in this population is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The SFH may be used after 12 weeks of gestation but its accuracy may be diminished by a multiple pregnancy, maternal size, intrauterine growth restriction, fetal position, and other maternal or fetal characteristics [9, 10, 11, 12]. Moreover, due to the observed variations in SFH across populations, local standards are required for optimal pregnancy dating using SFH [13, 14, 15, 16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…In fact, we believe that at least 21 different, locally derived SFH charts are currently being used in clinical practice worldwide 89 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29…”
Section: Introductionmentioning
confidence: 99%